Tolerogenic dendritic cells impede priming of naïve CD8+ T cells and deplete memory CD8+ T cells. Issue 1 (12th November 2012) - Kleijwegt, Fleur S.; Jansen, Diahann T. S. L.; Teeler, Josefine; Joosten, Antoinette M.; Laban, Sandra; Nikolic, Tatjana; Roep, Bart O.
<x xml:space="preserve">Abstract</x> Type 1 diabetes is a T‐cell‐mediated autoimmune disease in which autoreactive CD8+ T cells destroy the insulin‐producing pancreatic beta cells. Vitamin D3 and dexamethasone‐modulated dendritic cells (Combi‐DCs) loaded with islet antigens inducing islet‐specific regulatory CD4+ T cells may offer a tissue‐specific intervention therapy. The effect of Combi‐DCs on CD8+ T cells, however, remains unknown. To investigate the interaction of CD8+ T cells with Combi‐DCs presenting epitopes on HLA class I, naive, and memory CD8+ T cells were co‐cultured with DCs and proliferation and function of peptide‐specific T cells were analyzed. Antigen‐loaded Combi‐DCs were unable to prime naïve CD8+ T cells to proliferate, although a proportion of T cells converted to a memory phenotype. Moreover, expansion of CD8+ T cells that had been primed by mature monocyte‐derived DCs (moDCs) was curtailed by Combi‐DCs in co‐cultures. Combi‐DCs expanded memory T cells once, but CD8+ T‐cell numbers collapsed by subsequent re‐stimulation with Combi‐DCs. Our data point that (re)activation of CD8+ T cells by antigen‐pulsed Combi‐DCs does not promote, but rather deteriorates, CD8+ T‐cell immunity. Yet, Combi‐DCs pulsed with CD8+ T‐cell epitopes also act as targets of cytotoxicity, which is undesirable for survival of Combi‐DCs infused into patients in therapeutic immune intervention strategies.